Exploring Entrepreneurial Success Factors in Nepal - Mishra, A. K. (New Perspective: Journal of Business and Economics, 2024)
Entrepreneurship education plays a crucial role in fostering economic growth and competitiveness by providing individuals with the skills and knowledge necessary for success and innovation. Addressing educational needs, particularly in underserved regions, can significantly enhance entrepreneurial outcomes and contribute to broader economic development. Government policies and regulations profoundly impact business operations, competitiveness, and growth. It is essential for governments to continuously adapt their policies to create a conducive business environment and promote entrepreneurial development. The interplay between government policies and business performance underscores the importance of a well-coordinated approach to economic policy and entrepreneurship support. Effective policy frameworks are essential in supporting entrepreneurial activities and fostering a favorable business environment. The dynamic relationship between government actions and business success highlights the need for ongoing adaptation and coordination in economic policy to promote entrepreneurial development and economic growth.